Pengaruh Atribut Supermarket dan Motif Belanja Hedonik terhadap Loyalitas Konsumen pada Supermarket Foodmart Lembuswana Samarinda - Slamet Ariyadi; Suharno -; J. Kuleh (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
In this study, researchers used a sample size of between 10-25 times the number of independent variables. Ferdinand (2005: 74). Therefore, based on this formula, the number of samples required in this study is 2 x 25 = 50 respondents. The analytical method used is multiple linear regression analysis. Based on F test Simultaneous, independent variables that attribute supermarket and hedonic shopping motives are jointly (simultaneously) significantly affects the dependent variable that consumer loyalty Foodmart supermarket LembuswanaSamarinda, while based on partial t test (respectively) Independent variables: attribute significant impact supermarket customer loyalty Foodmart supermarket Lembuswana Samarinda and hedonic shopping motives significant effect on consumer loyalty Foodmart supermarket LembuswanaSamarinda.Keywords: Product Quality, Brand Image, Consumer Brand Loyalty